Implementation and Operational Research: Early Tracing of Children Lost to Follow-Up From Antiretroviral Treatment. (15th December 2015) - Ardura-Garcia, Cristina; Feldacker, Caryl; Tweya, Hannock; Chaweza, Thom; Kalulu, Mike; Phiri, Sam; Wang, Duolao; Weigel, Ralf
Abstract : Background: Loss to follow-up (LTFU) challenges the success of antiretroviral therapy (ART) scale-up among pediatric patients. Little is known about children who drop out of care. We aim to analyze risk factors for LTFU among children on ART, find their true outcomes through tracing, and investigate their final outcomes after resuming ART. Methods: This is a descriptive, retrospective, cohort study of children on ART between April 2006 and December 2010 in 2 clinics in urban Malawi. Routine data from an electronic data system were used and matched with information obtained through routine tracing procedures. Results: Of 985 children (1999 child-years) on ART, 251 were LTFU: 12.6/100 child-years. At ART initiation, wasting [adjusted hazard ratio (AHR) 1.58 and 95% confidence interval (CI): 1.02 to 2.44] was independently associated with higher risk of LTFU. Of 201 LTFU children traced, 79% were found: 11% died, 25% stopped, 26% transferred-out, and 37% were still on ART. Median time between last visit and first tracing was 84 days (interquartile range: 64–101 days). Tracing reduced risk of LTFU by 38% (AHR 0.62 and 95% CI: 0.42 to 0.91) and decreased LTFU from 23.2% to 8.5%. Additional outcomes of stop, death, and transfer-out increased 4.4-fold, 1.8-fold, and 1.3-fold, respectively. Traced children with gaps in ART intake who resumed ART had higher risk of stopping (AHR 4.92 and 95% CI: 1.67 to 14.5) and transfer out (AHR 2.70 and 95% CI: 1.75 to 4.17) as final outcome. Conclusions: Early tracing substantially reduces LTFU; approximately one-third presumed LTFU was found to be still on ART. Children with wasting at initiation and those traced and found to have irregular ART intake require targeted interventions. Abstract : Supplemental Digital Content is Available in the Text.